Ribavirin for Chronic Hepatitis E Virus Infection in Ibrutinib-Exposed Patients. (28th July 2019) - Protin, Caroline; Abravanel, Florence; Alric, Laurent; Tavitian, Suzanne; Obéric, Lucie; Izopet, Jacques; Martin-Blondel, Guillaume; Ysebaert, Loic
Abstract: Ibrutinib is an oral first-in-class Bruton's tyrosine kinase inhibitor approved for the therapy of various B-cell lymphoid malignancies. Among ibrutinib-related infections, viral hepatitis are poorly described. We report our single-center experience with 4 cases of chronic hepatitis E virus infection and their management with ribavirin.